Structural Style and Kinematic History of the Colombian Eastern Cordillera - Costantino, Diego; Paton, Douglas; Mora, Andrés (Frontiers in Earth Science, 2021)
Fold-and-thrust belts and their associated structures are amongst the most common geological features of convergent margins. They provide significant information about crustal shortening and mountain-building processes. In subaerial belts, where the erosional rates are high and the growth strata are mostly eroded, methodologies such as that presented here can provide insights into to their formation. Two 2D cross-sections located in the Eastern Cordillera of Colombia are presented in this research. These sections extend from the Bogota Savanna to The Llanos, parallel to the regional deformation direction. Section construction was carried out using commercial surface data, and seismic information provided by Ecopetrol. Published thermochronometric data, gravel-clast petrography analysis, and paleoflora analysis were used to construct a viable tectono-evolutionary history of the study area. This evolutionary model is presented here in two palinpastic restorations from the Early Cretaceous to Recent (~65 Ma to Present-day). Section 1 and Section 10 accumulated 17.3 km and 19.5 km of shortening, respectively. The section reconstruction displays two major tectonic events – post-rift subsidence during the Early-Mid Paleogene, and positive inversion from the Oligocene to Recent (~ 33 Ma to Present-day). This investigation focuses on the compressional period, where the structural analysis evidences an acceleration in the shortening rate, as well as a progressive migration of the deformation from northwest to southeast. This research discusses the extent and limitation of this methodology, as well as the principal structural aspects of the reconstruction.